Extremely low biodiversity Arctic intertidal habitats as sentinels for environmental change - Griffiths, Huw J.; Waller, Catherine L.; Roberts, Stephen J.; Jażdżewska, Anna M.; Hik, David S. (Frontiers in Marine Science, 2024)
The Arctic is undergoing dramatic changes, including an unprecedented decline in sea ice. Previous studies have shown the severe structuring impact of sea ice scour upon polar intertidal communities. A dramatic example of the influence of Arctic sea ice is the highly depauperate intertidal of Cambridge Bay (Iqaluktuuttiaq) on Victoria Island, Nunavut, Canada. Cambridge Bay intertidal is dominated by a single species of amphipod crustacean, Gammarus setosus, with rare examples of another amphipod, bivalve molluscs, and oligochaetes. Primary producers are limited to a thin algal film, with no macroalgae present shallower than 2 m water depth. This intertidal biodiversity has remained extremely low since it was first surveyed 70 years ago, however, the seasonal sea ice thickness has been in decline for over 50 years. Given the observed dramatic increases in biodiversity and biomass with decreased sea ice cover elsewhere in the Arctic and the presence of the Canadian High Arctic Research Station, we suggest that the intertidal of Cambridge Bay offers an ideal location for a low cost, low effort, and long-term monitoring of biodiversity change and tipping points that may be influenced by sea ice loss in the Arctic as part of a network intertidal monitoring stations.